ANALISIS EFEKTIVITAS PROGRAM BANTUAN LANGSUNG TUNAI DANA DESA TAHUN 2024: STUDI KASUS DI DESA KEDUNGJERUK, INDONESIA - Erlina Rusmawati , (Jurnal Cakrawala Ilmiah, 2025)
Background. Rural poverty remains a critical challenge in Indonesia, prompting the government to implement the Village Fund Direct Cash Assistance (BLT-DD) program to alleviate economic burdens on vulnerable populations post-pandemic. Objective. This study analyzes the effectiveness of the BLT-DD program implementation in Kedungjeruk Village, Mojogedang Sub-district, Karanganyar Regency, during 2024. Methods. A qualitative descriptive case study was conducted using Budiani's (2007) effectiveness theory with four indicators: target accuracy, program goal achievement, program socialization, and program evaluation. Data were collected through in-depth interviews with beneficiaries, village officials, and program implementers, supplemented by document analysis. Data validity was ensured through source and method triangulation. Results. The BLT-DD program demonstrated considerable effectiveness in Kedungjeruk Village. The program successfully targeted vulnerable groups including elderly, disabled individuals, chronically ill residents, orphans, and those who lost livelihoods. Assistance effectively supported beneficiaries' basic needs including consumption, healthcare, and education. Program socialization utilized direct community engagement approaches, while routine evaluations were conducted through village and hamlet-level deliberations. Conclusions. The BLT-DD program achieved its poverty alleviation objectives through proper targeting and community participation. However, improvements in data digitalization and participatory evaluation mechanisms are needed to optimize program effectiveness. These findings contribute to understanding social assistance program implementation in rural Indonesian contexts.